Acetylcholinesterase inhibitory activity of spices and culinary herbs. - Sathya, S.; Nilupa, R.A.; Lalith, J.; Yoshinori, F. (De Gruyter, 2022)
Cholinesterases play an important role in the area of neurobiology, toxicology, and pharmacology, out of which acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) are vital in nerve impulse transmission [1]. The enzyme AChE catalyzes the hydrolysis of the ester bond of acetylcholine to terminate the nerve impulse transmission at the cholinergic synapses [2]. Compounds that are capable of suppressing the activity of AChE are known as AChE inhibitors or anticholinesterases. Anticholinesterases inhibit AChE enzyme, thereby ......